On the series expansion of the spatial SIS evolution operator - J. Martins (2011)
For the spatial stochastic susceptible-infected-susceptible model, we consider the perturbative series expansion of the gap between the dominant and subdominant eigenvalues of the evolution operator. We compute explicitly the first terms of the series expansion of the gap with difference equations for the calculation of states.